Evaluation of the Compatibility of Organosolv Lignin-Graphene Nanoplatelets with Photo-Curable Polyurethane in Stereolithography 3D Printing - Ibrahim F.; Mohan D.; Sajab M.S.; Bakarudin S.B.; Kaco H. (MDPI AG, 2024)
Indexed by WOS/Scopus/ERA